Effect of captopril first doses on blood pressure and renal function in children with congestive cardiac failure. Issue 6 (1st February 2011) - Oualid, E; Wheeler, S; Mulla, H
Abstract : Aims and objectives: The aim of this retrospective study was to determine the frequency and severity of the effects of 'first dose' captopril on blood pressure and renal function in children with congestive cardiac failure. Methods: Retrospective data were collected from case notes, prescription and TPR charts of children treated between April 2007 and March 2009 at Glenfield Hospital, a tertiary paediatric cardiology unit. Blood pressure, urea, creatinine and potassium data were recorded precaptopril and postcaptopril test dose. If more than one test dose was given then data relating to additional doses was also collected. Concomitant diuretic therapy was also recorded. Hypotension was defined as a greater than 25% fall in systolic blood pressure (SBP). Results: Data from a total of 48 children were included in the analysis. The mean (range) test doses of captopril administered was 0.1 (0.05–0.22) mg/kg. The mean (range) discharge dose was 0.73 (0.29–1.2) mg/kg. The mean (SD) fall in SBP and diastolic blood pressure following the first dose was 12.3 (15.6) mm Hg (p<0.0005) and 10.8 (12.7) mm Hg (p<0.0005), respectively. Nine patients (18%) developed hypotension, one of whom had their captopril stopped. There was no significant difference between the ages of patients who developed hypotension. Predose and postdose biochemical assessment of renal function showed no effect of dosing: creatinine 44.06 (10.30) and 43.34 (12.54) mmol/l, respectively (p=0.13), urea 5.13 (2.49) and 5.06 (2.21) mmol/l, respectively (p=0.78). There were no a cases of acute renal failure. Further analysis of the BP data using dose-time response models estimated the time to peak drop in BP as 1.1 h, and recovery of blood pressure by 4–6 h. The dose at which 50% of the maximum drop in BP was achieved was estimated as 0.7 mg/kg. There was significant variability in the change in BP post dosing, time to peak effect and return to baseline. Conclusion: Captopril therapy is currently initiated in children as inpatients. However, the results of this audit reveal that only 18% of children experienced hypotension post dosing, with only one resulting in cessation of therapy. There was also no deterioration in renal function. These results suggest that it may be safe to initiate captopril therapy in primary care by GPs.